Assessment of the Opinions of Anesthesiology and Reanimation Research Assistants Regarding Clinical Anatomy Education: A University Example - Mustafa Büyükcavlak; Zeliha Fazlıoğulları; Nadire Ünver Doğan; İnci Kara; Emine Aslanlar (Genel Tıp Dergisi)
Introduction: Anatomy is considered one of the cornerstones of medical education. In-depth understanding of anatomy is essential, especially for safe clinical practice in surgical disciplines. This study aimed to evaluate the feedback of research assistants in the department of anesthesiology and reanimation, who received clinical anatomy education. Methods: Clinical anatomy education was provided for research assistants at different levels in the department of anesthesiology and reanimation, with two hours per week, and the education was completed within one month. The 5-point Likert scale questionnaire consisting of 18 questions was administered to research assistants to gather their opinions about education. Participants were asked to rate the questions on a scale from 1 to 5. Additionally, data such as age, gender, duration of clinical experience, experience with neuroaxial or peripheral nerve blocks, and participation in regional anesthesia courses were recorded. Results: A total of 40 participants, including 15 (37.5%) males and 25 (62.5%) females, with an average age of 29.67 ± 3.94 years, were included in the study. Nearly all participants in our study reported that integrated clinical anatomy education is necessary. The majority mentioned that anatomy education would contribute to airway management and regional anesthesia applications. The participation rate in regional anesthesia courses before education was 17.5%. There was no significant difference in average questionnaire scores between those who participated in regional anesthesia courses and those who did not (p=0.06). Conclusion: In the process of anesthesiology and reanimation specialization training, we believe that incorporating clinical anatomy education would enhance the quality of specialization education, thereby improving safety and effectiveness in clinical applications.